2022
DOI: 10.1111/his.14798
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic characterisation of HIV‐associated aggressive B‐cell non‐Hodgkin lymphomas, which do not occur specifically in this population: diagnostic and prognostic implications

Abstract: The frequency of aggressive subtypes of B‐cell non‐Hodgkin lymphoma (B‐NHL), such as high‐grade B‐cell lymphomas (HGBL) with MYC and BCL2 and/or BCL6 rearrangement (HGBL‐DH/TH) or Burkitt‐like lymphoma (BL) with 11q aberration, is not well known in the HIV setting. We aimed to characterise HIV‐associated aggressive B‐NHL according to the 2017 WHO criteria, and to identify genotypic and phenotypic features with prognostic impact. Seventy‐five HIV‐associated aggressive B‐NHL were studied by immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Of note in DLBCL cases, the frequency of BCL6 rearrangement (21%) was similar to those described in patients without HIV infection, whereas BCL2 rearrangement was infrequent (2.6%), with an incidence substantially lower than that reported in immunocompetent patients, in line with the study of Baptista et al. 25 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Of note in DLBCL cases, the frequency of BCL6 rearrangement (21%) was similar to those described in patients without HIV infection, whereas BCL2 rearrangement was infrequent (2.6%), with an incidence substantially lower than that reported in immunocompetent patients, in line with the study of Baptista et al. 25 …”
Section: Discussionsupporting
confidence: 87%
“…In the more recent cART era, only few data are available on the incidence, clinical characteristics, and outcome of SHL and DHL/THL in the setting of HIV. 22 , 23 , 24 , 25 Our study aims to analyze HIV-associated BCL, comparing those with or without MYC genetic alteration, associated or not to BCL2 and BCL6 translocations, from clinical presentation to treatment choice and survival outcome, to add knowledge in a field with really scanty information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predictive power of the molecular classification is uncertain, and some data suggested that it is not clinically relevant for prognosis in HIV-related DLBCL [ 40 ]. In contrast, most recent studies pointed out that HIV-related DLBCL cases with a non-germinal center phenotype tended to have a worse overall survival and progression-free survival than the cases with the germinal center phenotype [ 41 , 42 ].…”
Section: Pathological Characteristics and Etiopathogenesismentioning
confidence: 99%
“…This peculiar 11q-gain/loss aberration has been described to be particularly frequent in posttransplant patients, who develop B-cell lymphomas with Burkitt-like morphology [ 28 ]. It has also been described in the setting of HIV infection [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%